Fundoscopic Changes in Maroteaux-Lamy Syndrome - Augusto Magalhães; Jorge Meira; Ana Maria Cunha; Raul Jorge Moreira; Elisa Leão-Teles; Manuel Falcão; Jorge Breda; Fernando Falcão-Reis (Case Reports in Ophthalmological Medicine)
Purpose. To describe a clinical case of mucopolysaccharidosis type VI (MPS VI), or Maroteaux-Lamy syndrome, with fundoscopic alterations that may correspond to scleral deposits of glycosaminoglycans. Materials and Methods. Clinical case report. Results. A 16-year-old girl with MPS VI was examined at the Ophthalmology Department for poor vision due to opacified corneas. Treatment consisted of bilateral penetrating keratoplasty. Retinographies and enhanced depth imaging optical coherence tomography (EDI-OCT) were performed after surgery, suggesting the presence of scleral glycosaminoglycan deposits. The patient evolved with stable corneal and fundoscopic findings. Conclusions. To our knowledge, this is the first case of MPS VI described in vivo with suspected deposits of glycosaminoglycans in the sclera. Fundoscopic alterations are not usually included in the ocular pathological spectrum of MPS VI. However, with improved control of systemic comorbidities, survival rates of these patients have increased, which in turn has made it possible to observe other changes besides the ones that were classically described. Despite being particularly challenging to manage, efforts should be made to maximizing the visual acuity of these patients, in order to provide them the best possible quality of life.